Geometrical and magnetic properties of small titanium and chromium clusters on monolayer hexagonal boron nitride. Issue 8 (8th February 2023) - Hao, Dong; Wang, Yueyi; Tang, Xiangqian; Zhao, Xinjia; An, Yang; Wang, Wenyu; Li, Jianmei; Shan, Xinyan; Lu, Xinghua
Abstract : The Ti/Cr clusters, from dimers to pentamers, on a single-layer h-BN are investigated using first-principles calculations. The relatively weak interaction with the h-BN monolayer makes it possible to build versatile and interesting 3D nanostructures. Abstract : Magnetic clusters on an insulating substrate are potential candidates for spin-based quantum devices. Here we investigate the geometric, electronic, and magnetic structures of small Ti and Cr clusters, from dimers to pentamers, adsorbed on a single-layer hexagonal boron nitride (h-BN) sheet within the framework of density functional theory. The stable adsorption configurations of the Ti clusters and Cr clusters composed of the same number of atoms are found to be totally different from each other. The difference in their bonding mechanisms has been revealed by the density of states and the charge density difference of the corresponding adsorption systems. While chemical bonds are formed between the Ti atoms and the supporting sheet, the Cr clusters are found in the physisorption state on the substrate. In addition, it is shown that the h-BN sheet is energetically favorable for building three-dimensional Ti clusters. These findings support the use of h-BN as a suitable decoupling substrate for manipulation of quantum spin states in small transition metal (TM) clusters and fabrication of devices based on them.